Evaluation of Energy Use and Some Environmental Impacts for Greenhouse Tomato Production in the High Altitude Tropics (2006)
Greenhouse cultivation in the high altitude tropics is an important economical activity and the interest to invest in greenhouse technology to improve yield and quality is increasing. The evaluation of the energy use and other burdens associated with protected cultivation has to be accounted for in order to increase sustainability. The aim of this paper was to make a contribution to the applicability of the life cycle assessment (LCA) methodology in high tropics tomato greenhouse production as tool to identifity energy use and some environmental impacts, studying a case in the Bogotá Plateau (Colombia). Overall energy costs for tomato production were calculated at 1108.7 MJ·ton-1, which is extremely low when compared to the energy use in northern Europe. The land use indicator was estimated at 38.5 m2 ·y -1·t-1 and a water consumption of 28 L·kg-1. High potential emissions of N and P were estimated in relation with high concentrations applied in nutrient solutions and an elevated water use. Improvements in tomato yields and water use efficiency, enhancing the level of technology, are the key factors for reducing environmental impact. The adaptation of impact indicators will be necessary to apply LCA methodology in high tropical farming systems.